When care transcends the human: Afrodescendant women and their defense of common goods in Bocas del Palo community council - Pinzón Pinzón, Federico (Sociedad y Economía, 2025)
This paper reports on the struggle of women from the Afro-descendant community at Bocas del Palo Council (Jamundí, Colombia) in a context of deep inequalities and injustice. From the perspective of the ethics of care and socio-ecological justice, we explore herein how these women have developed resistance against environmental conflicts and, how through their worldviews and community organization, they have safeguarded both their community’s well-being and the natural environment. By combining qualitative and spatial methods, this study shows that their leadership has fostered alternative approaches to territorial management by integrating care for nature as a central dimension of justice and gender struggles. The findings also reveal how the actions of the community council have contributed to ecosystem conservation and have established an alternative strategy for defending and managing common goods in a territory marked by severe environmental conflicts.